1996
DOI: 10.1042/bj3190529
|View full text |Cite
|
Sign up to set email alerts
|

Changes induced by fasting and dietetic obesity in thermogenic parameters of rat brown adipose tissue mitochondrial subpopulations

Abstract: The effects of starvation on the thermogenic parameters of three different mitochondrial subpopulations in brown adipose tissue (BAT) of both post-cafeteria obese and lean rats were investigated. Tissue from different BAT depots from fed and 24 h starved rats were collected, pooled and three mitochondrial subpopulations were isolated by differential centrifugation; the M1 fraction (1000 g), the M3 fraction (3000 g) and the M15 fraction (15,000 g). Thermogenic parameters were measured in the three mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 41 publications
(62 reference statements)
4
21
0
2
Order By: Relevance
“…All these results give possible explanation to decreased activity of BAT function and characteristics upon CI treatment, but may not be implicated for changed BAT phenotype. Our results collates very well with the study conducted by Matamala and coworkers, where authors have demonstrated that lack of BAT response in obese rat is due to the change in mitochondria subpopulation and it was different from lean rat (Matamala et al 1996). The above literature provides coherent evidence to suggest that CI treatment may also change the mitochondrial subpopulation leading to decrease the metabolic activity of brown adipocytes.…”
Section: Figuresupporting
confidence: 34%
“…All these results give possible explanation to decreased activity of BAT function and characteristics upon CI treatment, but may not be implicated for changed BAT phenotype. Our results collates very well with the study conducted by Matamala and coworkers, where authors have demonstrated that lack of BAT response in obese rat is due to the change in mitochondria subpopulation and it was different from lean rat (Matamala et al 1996). The above literature provides coherent evidence to suggest that CI treatment may also change the mitochondrial subpopulation leading to decrease the metabolic activity of brown adipocytes.…”
Section: Figuresupporting
confidence: 34%
“…A connection between mitochondrial biogenesis and the mitochondrial fractions has been suggested, which would imply that the lightest mitochondria would act as transitional forms of the heaviest, i.e., more differentiated ones [39][40][41][42][43][44]. This fact renders the mitochondrial subpopulations a suitable tool for the study of mitochondriogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…8,20 Obesity affects the expression and regulation of molecules involved in energy homeostasis and body weight maintenance. [21][22][23] Adiponutrin and ATGL mRNA expression has been described to be altered in adipose tissue of animal models of genetic obesity, 2,7,10 and it has been demonstrated that two human adiponutrin polymorphisms are associated with obesity. 9,24 In addition, our group has reported that adiponutrin nutritional regulation is impaired in obese Zucker rats 10 and that fasting upregulation of ATGL in white adipose tissue is impaired in old rats, which could be related to the weight gain that occurs with aging.…”
Section: Introductionmentioning
confidence: 99%